The Problems of Women's Participation in Political Parties - Atikah Rahmi (International Journal Reglement & Society (IJRS), 2022)
The participation of Indonesian women in political parties is still minimal, so it correlates with the low number of women's representation in parliament. Based on data from the World Bank, Indonesia is ranked 7th in Southeast Asia for women's representation in parliament. The low number of women's representation in parliament has implications for policy issues related to gender equality and the lack of response to the main problems faced by women. The problem of women's participation in political parties needs to be studied from a legal perspective, so that the factors behind the lack of women's representation are known. Women's participation in political parties is a place and starting point for women to enter the electoral process. The research method used is normative juridical. The results of the study indicate that there are many factors that cause the lack of women's participation in political parties, one of which is the stigma that discredits women's position in leading and making decisions in the state process. So it needs to be encouraged from the perspective of norms to implementation